The Principal's Strategy in Implementing the Value of Religious Moderation in the Pancasila Student Profile Strengthening Project - Rifki, Muhammad; Ma`arif, Muhammad Anas; Rahmi, Sri; Rokhman, Mauhibur (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
The issue of intolerance and radicalism among students must be taken seriously by school principals, who play a crucial role in managing the learning process, including in the P5 program. This research analyses the principal’s strategy in implementing the value of religious moderation in P5 and its implications for student character and school culture. This study is a qualitative research project using a case study method. Data collection methods included interviews, observations, and documentation, and the data were analyzed through reduction, presentation, and conclusion. Data verification was achieved through triangulation of sources and methods. The research results show that the principal's strategy for implementing the value of religious moderation in P5 involves three main approaches: process, program, and culture strategies. The process strategy includes planning, implementation, evaluation, and follow-up. The program strategy encompasses structuring P5 activities based on teamwork and partnerships with external parties. Meanwhile, the cultural strategy utilizes habituation activities to support the values and meaning of moderation within P5. The strategy implemented has had implications for student character, fostering awareness, tolerance, care, love for the country, and teamwork. Additionally, they have promoted a disciplined and collaborative school culture.